2014
DOI: 10.1042/cs20130660
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin 1 is critical for abdominal aortic aneurysm formation induced by angiotensin II and inhibition of lysyl oxidase

Abstract: Although angiotensin II (Ang II) and its receptor AT1 have been implicated in abdominal aortic aneurysm (AAA) formation, the proximal signaling events primarily responsible for AAA formation remain uncertain. Caveolae are cholesterol-rich membrane microdomains that serve as a signaling platform to facilitate the temporal and spatial localization of signal transduction events including those stimulated by Ang II. Caveolin-1 (Cav1) enriched caveolae in vascular smooth muscle cells mediate ADAM17-dependent epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 72 publications
3
35
2
Order By: Relevance
“…While BAPN treatment alone does not promote AAA, it causes AAA development and rupture when combined with AngII via degeneration of elastic lamina 12 . In VSMCs, both ADAM17 and EGFR co-localize at caveolae, and AAA formation induced by AngII plus BAPN was attenuated in caveolin-1 deficient mice 13 . Moreover, we have recently reported that pharmacological inhibition of EGFR prevents AAA development induced by AngII plus BAPN, which was associated with suppression of ER stress, oxidative stress, and interleukin-6 and MMP-2 expression 10 .…”
Section: Introductionmentioning
confidence: 93%
“…While BAPN treatment alone does not promote AAA, it causes AAA development and rupture when combined with AngII via degeneration of elastic lamina 12 . In VSMCs, both ADAM17 and EGFR co-localize at caveolae, and AAA formation induced by AngII plus BAPN was attenuated in caveolin-1 deficient mice 13 . Moreover, we have recently reported that pharmacological inhibition of EGFR prevents AAA development induced by AngII plus BAPN, which was associated with suppression of ER stress, oxidative stress, and interleukin-6 and MMP-2 expression 10 .…”
Section: Introductionmentioning
confidence: 93%
“…Overexpression of caveolin-1 (Cav1), the major structural protein of caveolae, prevents ANG II-induced hypertrophy and migration of VSMCs through suppression of HB-EGF shedding, EGFR transactivation, and ERK activation (534). However, Cav1 silencing is also protective against EGFR transactivation, suggesting a tight regulatory component via Cav1/caveolae may be critical for EGFR transactivation (535).…”
Section: Role Of Egfr In the Vasculaturementioning
confidence: 99%
“…Nonetheless, caveolin-1 also appears essential in EGFR transactivation: silencing caveolin-1 expression inhibits Ang II-induced EGFR transactivation in vascular tissue (Takayanagi et al, 2014); caveolin-1 deletion inhibits EGFR transactivation by TGF- in hepatocytes, in association with failed TACE/ADAM17 activation (Moreno-Caceres et al, 2014); and caveolin-1 deletion or caveolar disruption abolishes stretch-dependent EGFR transactivation and Akt signalling in mesangial cells (Zhang et al, 2007). Caveolin-1 may thus act to limit EGFR activity in the basal state whilst promoting EGFR transactivation.…”
Section: Cell Membrane Localisation -Membrane Rafts Caveolae and Cavmentioning
confidence: 99%